Intergovernmental relations for public health adaptation to climate change in the federalist states of Canada and Germany. (September 2018) - Austin, Stephanie E.; Ford, James D.; Berrang-Ford, Lea; Biesbroek, Robbert; Tosun, Jale; Ross, Nancy A.
Highlights: Canadian and German intergovernmental relations for health adaptation are studied. Federal-regional relationships for adaptation follow federalism patterns. Regional-local relationships for adaptation deviate from federalism patterns. Examining other countries' approaches to health adaptation can promote learning. Abstract: Climate change is a significant threat to public health, and governments at all scales will need to adapt to protect the health of their populations. The impacts of climate change are highly localized and thus federal systems theoretically have the inherent advantage of allowing for regional diversity and policy experimentation in adaptation. However, there are also higher levels of conflict and stalemates in federal systems than in unitary systems, complicating intergovernmental relations and coordination necessary for public health adaptation. We examine how intergovernmental dynamics are patterned across national, regional and local levels of government for public health adaptation to climate change, drawing upon semi-structured interviews (n = 28) in comparative embedded case studies of Canada and Germany. We find that coordination between levels of government specifically for climate change and health is rare, but climate change issues are occasionally discussed through working groups or through existing methods of public health coordination. These findings have implications for national and regional governments in federal systems seeking to enable sub-national public health adaptation to climate change and create synergies between levels of government.